Segmentation of the housing market with internet data: Evidence from Denmark - Jakob Feveile Adolfsen; Bjarke Mørch Mønsted; Adrian Michael Bay Schmith; Alessandro Tang-Andersen Martinello; Simon Gudiksen; Kasper Fredløv Sonberg (Danmarks Nationalbank, 2022)
In this paper, we introduce a novel tool for housing market analysis developed on the basis of online listings data from the largest real estate listing site in Denmark. The tool uses a combination of machine learning techniques to provide a datadriven segmentation of the housing market into meaningful submarkets that differ from administrative classifications. We demonstrate how the tool can support monitoring and research of underlying housing market developments in Denmark.
Keywords: 330; Housing market; internet data; neural network